Analisis Prosedur Penyelesaian Perselisihan Hubungan Industrial: Studi Kasus PHK Sepihak di PT Goodyear Indonesia - Martinus Alexander Simanjuntak; Dista Aulia Y; Zahra Utami Aprilia; Pipi Susanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This article analyzes the legality and procedural aspects of industrial dispute resolution in the case of unilateral termination of employment involving 44 employees by PT Goodyear Indonesia. Using a normative juridical approach and case study method, the author examines whether the termination aligns with Law Number 11 of 2020 on Job Creation and the dispute resolution mechanism under Law Number 2 of 2004. The findings reveal that the termination failed to meet both procedural and substantive legal standards. The company did not involve workers in bipartite negotiations, failed to provide written notice in accordance with Government Regulation No. 35 of 2021, and did not fulfill the workers' entitlements. The Industrial Relations Court in Bandung ultimately annulled the termination and ordered the restoration of workers' rights. This study emphasizes the importance of legal compliance in industrial relations to safeguard workers' rights and ensure legal certainty.